Arab-Zionist Struggle Terminology of Place Naming - Abu Own, Amal Mahmoud; Al-Deek, Ihsan Yacoub (Journal of Humanities & Social Sciences, 2024)
The thesis deals with the Arab-Zionist struggle terminology through studying and examining certain examples related to the struggle. It adopts an analytical-interpretive study of these examples in terms of their linguistic significance and their explicit or implicit intellectual dimensions. It also compares their usage by the two sides of the struggle, in an aim of addressing the problem of the study represented by the Zionist movement’s use of the terminology to support its narrative, and the weakness or failure of Arabic terms to confront the Zionist ones.The research focuses on the Zionist terminology, which manipulated the place-indicating terminology to impose Zionist narrative on the ground. And in order to form a comprehensive picture of the use of terms and their role in the conflict, the thesis is divided into three chapters as follows: the place-indicating terminology of the Zionist side, the Arab side’s attitude towards the Zionist terminology, and the significance of the terms used by both parties. The research results indicate that the Arab side adhered to the terminology existed before the occupation, but was sometimes forced to use the terminology of the Zionist side because it has become an imposed reality. The researchers recommended to intensify the efforts to spread awareness among the new generations to avoid using Zionist terminology, and to produce maps that include Arabic names and promote them through digital platforms.
Keywords: Palestine; Arab-Zionist Struggle; Zionist Narrative; Palestinian Narrative